2001, a Texas Folklore Odyssey (University of North Texas Press, 2001)
This volume of the Publications of the Texas Folklore Society "contains a sample of the research that members of the Society were doing at the turn of the millennium as represented at the 1998, 1999, and 2000 meetings." The volume covers "a wide variety of contemporary and historical topics," including baby lore, stories about notable women, stories about food and cooking, information about the Model T Ford, and more.